Retinal and preretinal localisation of epidermal growth factor, transforming growth factor alpha, and their receptor in proliferative diabetic retinopathy. Issue 9 (September 1994) - Patel, B; Hiscott, P; Charteris, D; Mather, J; McLeod, D; Boulton, M
Abstract : A number of growth factors have been implicated in the development and perpetuation of preretinal fibrovascular membranes in patients with proliferative diabetic retinopathy (PDR). The aim of this study was to determine the potential role of epidermal growth factor (EGF), transforming growth factor alpha (TGF-alpha), and their receptor (EGF-R) in PDR development. Immunostaining for EGF, TGF-alpha, and EGF-R was compared between normal retina, PDR retina, and PDR preretinal membranes. Weak staining for EGF and EGF-R was observed throughout the neural retina from non-diabetic eyes while weak to moderate staining for TGF-alpha was observed in the ganglion cell layer and the inner and outer nuclear layers. In contrast, intense staining for EGF and TGF-alpha and moderate staining for EGF-R were observed throughout the PDR retina. Immunoreactivity for EGF, TGF-alpha, and EGF-R was seen in the majority of the 11 excised membranes studied and, though variable, was generally greater than that observed in normal retinas. These results suggest an autocrine/paracrine role for EGF, TGF-alpha, and EGF-R in PDR.